(untitled) (Ameghiniana, 2013)
Seven species of Ostracoda, of which 5 are new, are described from strata of presumed Barremian age from Neuquén. They occur in association with such tipical "Wealden facies" Ostracoda as Cypridea and the charophytes Atopochara triuolois aff. triquetra and Triclypella aff. calcitrapa. A specie of Euestheria is also described.